Granular metamaterials with dynamic bond reconfiguration - Meng, Zhiqiang (2025)
Biological materials dynamically reconfigure their underlying structures in response to stimuli, achieving adaptability and multifunctionality. Conversely, mechanical metamaterials have fixed interunit connections that restrict adaptability and reconfiguration. This study introduces granular metamaterials composed of discrete bimaterial structured particles that transition between assembled and unassembled states through mechanical compression and thermal stimuli. These materials enable dynamic bond reconfiguration, allowing reversible bond breaking and formation, similar to natural systems. Leveraging their discrete nature, these materials can adaptively reconfigure their shape and respond dynamically to varying conditions. Our investigations reveal that these granular metamaterials can substantially alter their mechanical properties, like compression, shearing, and bending, offering tunable mechanical characteristics across different states. Furthermore, they exhibit collective behaviors like directional movement, object capture, transportation, and gap crossing, showcasing their potential for reprogrammable functionalities. This work highlights the dynamic reconfigurability and robust adaptability of granular metamaterials, expanding their potential in responsive architecture and autonomous robotics.